Peran kepercayaan, manfaat dan religiusitas dalam meningkatkan niat menggunakan kembali dompet digital - Adinda Ridhia A.N; Yudi Sutarso (STIE Perbanas Surabaya, 2020)
The purpose of this study is to examine the effect of trust and perceived value on continuance intention of payment gateway services with religiosity as moderation variable. This study involves 130 respondents collected through questionnaires in the area of Surabaya and Sidoarjo, East Java. Their responses were analyzed using descriptive analysis with SPSS 16.0 and statistical analysis with WarpPLS 6.0. The results indicate that trust and perceived benefit have positive effect on continuance intention. The moderating role of religiosity has an effect on the relationship between trust and continuance intention. It can be impliead that wallet payment companies should develop their strategies in the future, especially as an evaluation of the performance of their services in fintech competition. They should also provide important information to wallet payment so that they can build trust and perceived benefit that have an impact on continuance intetntion by moderating religiosity to increase the use of wallet payment services.